Microscale evaluation of laser cladded Inconel 625 exposed at high temperature in air. (15th January 2017) - Verdi, D.; Garrido, M.A.; Múnez, C.J.; Poza, P.
Abstract: Ni-based superalloys offer resistance to high-temperature oxidation in different industrial sectors. These alloys can also be deposited as coatings onto metallic substrates by means of different techniques. In this work, a diode laser with carefully selected process parameters was used to generate Inconel 625 coatings onto ferritic and stainless steel substrates. The coatings obtained were exposed to high-temperature treatment in air and different exposition times were studied. The evolution of the coatings microstructure was analysed and depth-sensing indentation tests were performed to measure the evolution of elastic modulus and hardness with the exposition time. Finally, mechanical properties and microstructural changes were correlated. The results revealed that the average mechanical properties and the microstructure of the coatings were not affected by the steel used as the substrate. The treatment at 520 °C increased the amount of carbides and brought to the appearance of Laves phases. The treatment at 800 °C promoted the formation of mainly δ and Laves phases. These microstructural evolutions involved changes in the values of the mechanical properties of the coatings, which could control their response under operating conditions. Graphical abstract: Highlights: The dendritic microstructure of the Inconel 625 clads was modified as a result of the high-temperatures exposition in air. The exposition to high temperature produced the formation of carbides and secondary phases in the interdendritic zones. The clads treated at high temperature showed higher values of elastic modulus and hardness than those as-deposited. Higher values of elastic modulus and hardness were measured after the heat treatment at 520°C than to 800°C. The elastic modulus of the secondary phases and carbides generated at high temperature were estimated.